ETOS KERJA KRISTEN DALAM BUDAYA PERKANTORAN DENGAN PERSPEKTIF TEOLOGI DAN SOSIOLOGI KRISTEN DI FAKULTAS TEOLOGI - Oktaviani Amanda Mangamba; Dedianto Ippang; Arta Sasta Paembong; Eqy Christian (CV. ADIBA AISHA AMIRA, 2025)
A Christian work ethic is an important aspect in shaping an office culture rooted in faith values ​​while addressing the demands of modern professionalism. This article aims to analyze the Christian work ethic in the context of office culture at the Faculty of Theology through the perspectives of Christian theology and sociology. The research uses a descriptive qualitative approach with a library study method, namely reviewing relevant literature related to work ethic, service management, and institutional culture. The results of the analysis indicate that the Christian work ethic is understood as a call of faith that integrates work with the dimensions of worship and service to God. From a Christian sociological perspective, office culture is seen as a space for social interaction that must be built on the basis of solidarity, love, and justice. The integration of theological values ​​​​and professionalism shows that work is not only a means to achieve targets, but also a manifestation of faith testimony. The main implication of the implementation of the Christian work ethic is the formation of the institutional identity of the Faculty of Theology that emphasizes integrity, service, and social transformation. Thus, the Christian work ethic becomes a moral and spiritual foundation that strengthens the role of the Faculty of Theology as an agent of renewal in the world of higher education.